Methylation of Tat by PRMT6 Regulates Human Immunodeficiency Virus Type 1 Gene Expression - Boulanger, Marie-Chloé (American Society for Microbiology, 2005)
The human immunodeficiency virus (HIV) transactivator protein, Tat, stimulates transcription from the viral long terminal repeats via an arginine-rich transactivating domain. Since arginines are often known to be methylated, we investigated whether HIV type 1 (HIV-1) Tat was a substrate for known protein arginine methyltransferases (PRMTs). Here we identify Tat as a substrate for the arginine methyltransferase, PRMT6. Tat is specifically associated with and methylated by PRMT6 within cells. Overexpression of wild-type PRMT6, but not a methylase-inactive PRMT6 mutant, decreased Tat transactivation of an HIV-1 long terminal repeat luciferase reporter plasmid in a dose-dependent manner. Knocking down PRMT6 consistently increased HIV-1 production in HEK293T cells and also led to increased viral infectiousness as shown in multinuclear activation of a galactosidase indicator assays. Our study demonstrates that arginine methylation of Tat negatively regulates its transactivation activity and that PRMT6 acts as a restriction factor for HIV replication.